Tipografi sebagai Alat Penyampaian Narasi Dystopia: Studi Tipografi pada serial Televisi Severance - Mansoor, Alvanov Zpalanzani; Juliansyah, Muhammad Kasyfi Hazazi (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
The Severance (2022) series, available on Apple TV+, uses typography as an important element in reinforcing the themes and narrative developed. This study aims to analyze how the typography in the series functions as a narrative tool for conveying major themes such as control, alienation, and identity separation. Using Peirce's visual semiotics theory, this research examines how the use of monotype typography, elegant serifs, and other graphic design elements convey deeper meanings beyond just plain text. Typography in Severance not only functions as a tool for text communication but also creates a profound visual impression, depicting a highly organized and tension-filled workplace. This study identifies how graphic design, particularly typography, creates a deep dystopian atmosphere and helps strengthen the existing narrative. Furthermore, in 2023, Severance was nominated for a Hugo Award in the Best Dramatic Presentation category, recognizing the quality of the series' production, including the use of graphic design that supports the major themes of the story. By analyzing various scenes, this study demonstrates how typography plays a crucial role in strengthening the narrative and creating an atmosphere filled with tension and control in Severance.